Neurophysiological Signatures of Motor Impairment in Patients with Rett Syndrome. Issue 5 (17th March 2020) - Bernardo, Pia; Cobb, Stuart; Coppola, Antonietta; Tomasevic, Leo; Di Lazzaro, Vincenzo; Bravaccio, Carmela; Manganelli, Fiore; Dubbioso, Raffaele
Abstract : Objective: Rett syndrome (RTT) is an X‐linked dominant neurodevelopmental disorder due to pathogenic mutations in the MECP2 gene. Motor impairment constitutes the core diagnostic feature of RTT. Preclinical studies have consistently demonstrated alteration of excitation/inhibition (E/I) balance and aberrant synaptic plasticity at the cortical level. We aimed to understand neurobiological mechanisms underlying motor deficit by assessing in vivo synaptic plasticity and E/I balance in the primary motor cortex (M1). Methods: In 14 patients with typical RTT, 9 epilepsy control patients, and 11 healthy controls, we applied paired‐pulse transcranial magnetic stimulation (TMS) protocols to evaluate the excitation index, a biomarker reflecting the contribution of inhibitory and facilitatory circuits in M1. Intermittent TMS‐theta burst stimulation was used to probe long‐term potentiation (LTP)‐like plasticity in M1. Motor impairment, assessed by ad hoc clinical scales, was correlated with neurophysiological metrics. Results: RTT patients displayed a significant increase of the excitation index ( p  = 0.003), as demonstrated by the reduction of short‐interval intracortical inhibition and increase of intracortical facilitation, suggesting a shift toward cortical excitation likely due to GABAergic dysfunction. Impairment of inhibitory circuits was also confirmed by the reduction of long‐interval intracortical inhibition ( p  = 0.002). LTP‐like plasticity in M1 was abolished ( p  = 0.008) and scaled with motor disability (all p  = 0.003). Interpretation: TMS is a method that can be used to assess cortical motor function in RTT patients. Our findings support the introduction of TMS measures in clinical and research settings to monitor the progression of motor deficit and response to treatment. ANN NEUROL 2020;87:763–773